ONLINE SOCIAL MEDIA ACCESSION AND HEALTH LITERACY OF GENERATION Y - พุทธิไสย, ดุสิดา; ศศิธนากรแก้ว, ศรัณย์ธร (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The objectives of this research were (1) to study the behavior of Generation Y’s online social media accession of The Department of Health according to demographic characteristics ; (2) to study Generation Y’s health literacy level; and (3) to study the relationships between health literacy, health accession, understanding, interacting, decision making, changing behavior, applying and sharing of information. The quantitative research methodology was applied to four hundred sampling population of Generation Y who had accessed to online social media of The Department of Health. The sample were selected using convenience sampling method. The online survey was constructed and used as a tool for collecting data. The statistics used to analyze the data were descriptive statistical analysis and inferential statistical analysis. The results of this research were as follows: in comparison of demographic characteristics, people at the different educational levels, occupations, and income had different access to online social media. In health literacy level, most studied population’s health accession was at medium level. However with health accession, understanding, interacting, decision making, changing behavior, applying and sharing of information were at high level. For the result of hypothesis testing, it was found that online social media accession has correlated with health literacy, interaction, decision making, changing behavior, applying and sharing of information with statistical significance at 0.01 level.